46 The Development and Evaluation of the Greater Manchester Heart Failure Investigation Tool (GM-HFIT): A Catalyst for Service Improvement. (6th June 2015) - Burey, Lorraine; Lewthwaite, Kieley; Terry, Dan; Lacey, Sam; Katy, Rothwell; Humphreys, John; Adams, Jack; O'Donnell, Caroline; Cook, Penny; Deaton, Christi; Astin, Felicity
Abstract : Introduction: Heart failure (HF) is a complex and highly debilitating clinical syndrome. Clear guidelines identify the optimum management of patients living with HF in primary settings but implementation of these is suboptimal. Aim: The aim of this service improvement project was to develop a tool kit, The Greater Manchester Heart Failure Investigation Tool (GM-HFIT), to improve the ongoing management of people diagnosed with HF. Methods: The GM-HFIT development was informed by the Promoting Action on Research Implementation in Health Services (PARIHS) framework. A prospective, pre-test, post-test design informed an audit conducted between 13 th February 2012 and 12 th December 2013 with data from two clinical commissioning groups (CCGs) across North West Manchester. Results: Data from 1146 matched cases were analysed using McNemar tests (SPSS v20). Preliminary analysis suggests that at baseline, 22% of patients were not eligible to be on the HF register, which decreased to 15% after introduction of the tool (P < 0.001). The recording of blood pressure (BP) was high at both time points (95%), while the recording of pulse and rhythm improved from 58% to 64% and 44% to 49% respectively (P = 0.005). While control of BP remained the same (with 62% of patients with target BP <130/70), the proportion of patients receiving the target dose of ACE Inhibitors and beta blockers improved significantly (70% to 85% and 68% to 85% respectively, P < 0.001). In addition 578 missing patients were added to the heart failure register as a result of the case finding element of the project and a further 6 were recommended for further investigation before adding. Conclusion: The GM-HFIT service improvment project led to improvements in identification and management of patients with HF in primary care.